The Impact of Using Lean Accounting Techniques on Evaluating Sustainable Performance in Economic Units in Iraq - Khudhur Abbas Jabbar Aefri (Green Economics: International Journal of Islamic and Economic Education, 2025)
This study aims to explore the impact of lean accounting techniques (henceforth, LATs) on enhancing sustainable performance in Iraqi economic units. Research has been conducted in the industrial sector because it is the right place to use these technologies. Thus, the Iraqi State Company of Vegetable Oils was chosen as the sample of analysis by randomly selecting 150 employees. To collect data, a questionnaire has been designed. Research design included the analysis of questionnaire data using advanced statistical techniques. Results showed that the application of lean accounting technology contributes significantly to improving the financial, social, and environmental performance of industrial companies in Iraq. The study recommends integrating LATs into economic units and training employees on their use to sustain performance and achieve competitive advantages.